Lessons from animal models of endocrine disorders caused by defects of protein folding in the secretory pathway. (1st January 2020) - Morishita, Yoshiaki; Arvan, Peter
Abstract: Most peptide hormones originate from secretory protein precursors synthesized within the endoplasmic reticulum (ER). In this specialized organelle, the newly-made prohormones must fold to their native state. Completion of prohormone folding usually occurs prior to migration through the secretory pathway, as unfolded/misfolded prohormones are retained by mechanisms collectively known as ER quality control. Not only do most monomeric prohormones need to fold properly, but many also dimerize or oligomerize within the ER. If oligomerization occurs before completion of monomer folding then when a poorly folded peptide prohormone is retained by quality control mechanisms, it may confer ER retention upon its oligomerization partners. Conversely, oligomerization between well-folded and improperly folded partners might help to override ER quality control, resulting in rescue of misfolded forms. Both scenarios appear to be possible in different animal models of endocrine disorders caused by genetic defects of protein folding in the secretory pathway. In this paper, we briefly review three such conditions, including familial neurohypophyseal diabetes insipidus, insulin-deficient diabetes mellitus, and hypothyroidism with defective thyroglobulin.